Influenza A/H1N1v in pregnancy: an investigation of the characteristics and management of affected women and the relationship to pregnancy outcomes for mother and infant. - Yates, L; Pierce, M; Stephens, S; Mill, A; Spark, P; Kurinczuk, J; Valappil, M; Brocklehurst, P; Thomas, S; Knight, M (2010)
BACKGROUND: In April 2009 a novel influenza A virus (AH1N1v) of swine origin (swine flu) emerged, spreading rapidly and achieving pandemic status in June 2009. Pregnant women were identified as being at high risk of severe influenza-related complications and as a priority group for vaccination against AH1N1v. Limited information was available about the maternal and fetal risks of AH1N1v infection or of antiviral drug or AH1N1v vaccine use in pregnancy. OBJECTIVES: To assess rates of and risk factors for adverse outcomes following AH1N1v infection in pregnancy and to assess the adverse effects of the antiviral drugs and vaccines used in prevention and management. METHODS: Prospective national cohort studies were conducted to identify pregnant women who were (1) suspected to be infected with AH1N1v or being treated with antiviral medication in primary care; (2) vaccinated against AH1N1v; and (3) admitted to hospital with confirmed AH1N1v. Characteristics of women with influenza-like illness (ILI) in primary care were compared with those of women without symptoms accepting or declining immunisation. Characteristics of women admitted to hospital with confirmed AH1N1v infection in pregnancy were compared with a historical cohort of over 1200 women giving birth in the UK who were uninfected with AH1N1v. Outcomes examined in hospitalised women included maternal death, admission to an intensive care unit, perinatal mortality and preterm birth. Risk factors for hospital and intensive care unit admission were examined in a full regression model. RESULTS: The weekly incidence of ILI among pregnant women averaged 51/100,000 over the study period. Antiviral drugs were offered to 4.8% [95% confidence interval (CI) 4.0% to 5.9%] and vaccination to 64.8% (95% CI 64.7% to 68.9%) of registered pregnant women. Ninety pregnant women with ILI presenting in primary care were reported to the research team, 55 of whom were prescribed antiviral drugs and in 42 (76%) cases this was within 2 days of symptom onset. After comparison with 1329 uninfected pregnant women offered vaccination, pre-existing asthma was the only maternal factor identified as increasing risk of ILI presentation [adjusted odds ratio (OR) 2.0, 95% CI 1.0 to 3.9]. Maternal obesity and smoking during pregnancy were also associated with hospital admission with AH1N1v infection. Overall, 241 pregnant women were admitted to hospital with laboratory-confirmed AH1N1v infection. Eighty-three per cent of these women were treated with antiviral agents, but only 6% received antiviral treatment before hospital admission. Treatment within 2 days of symptom onset was associated with an 84% reduction in the odds of admission to an intensive therapy unit (OR 0.16, 95% CI 0.08 to 0.34). Women admitted to hospital with AH1N1v infection were more likely to deliver preterm; a three times increased risk was suggested compared with an uninfected population cohort (OR 3.1, 95% CI 2.1 to 4.5). CONCLUSIONS: Earlier treatment with antiviral agents is associated with improved outcomes for pregnant women and further actions are needed in future pandemics to ensure that antiviral agents and vaccines are provided promptly to pregnant women, particularly in the primary care setting. Further research is needed on longer-term outcomes for infants exposed to AH1N1v influenza, antiviral drugs or vaccines during pregnancy.